THE ATTITUDE OF THE SUBJECT IN PERSONALITY TESTING. - Vernon, Philip E. (Journal of Applied Psychology)
The article enumerates various incentives or factors which have been employed for producing cooperation on the part of subjects in personality testing. Among the factors studied include competition, economic reasons, miscellaneous obligations, personal interest, interesting material and indirect incentives. It reveals that the reliability and validity of a pragmatic, empirical approach is determined by the usual statistical methods. However, there are claims that the empirical approach does not account the meaning of the test for the subject and the psychological factors which motivate his response. Counter arguments to this claim states that this objection was always acknowledged and the mentality of the subject is invariably considered by the psychologist who devises the test.